The development and evaluation of a questionnaire to assess the impact of vulval intraepithelial neoplasia: a questionnaire study. Issue 9 (10th April 2013) - Lockhart, J; Gray, NM; Cruickshank, ME
<x xml:space="preserve">Abstract</x> Objective To develop and evaluate a questionnaire to assess the burden of vulval intraepithelial neoplasia (VIN) in women. Design A questionnaire development study. Setting Vulval Disorders Clinic serving a regional population. Sample Fifty‐eight women with a histological diagnosis of VIN registered with the Vulval Disorders Clinic. Methods A 37‐item questionnaire was developed through a comprehensive literature review, consultation with specialist clinicians and pretesting to assess the burden experienced by women. The questionnaire was assessed for validity and reliability against existing questionnaires used in related disease areas. Main outcome measures Spearman correlations were calculated between items in the VIN questionnaire with the scores of the Dermatology Life Quality Index (DLQI), Hospital Anxiety and Depression Scale (HADS), Sabbatsberg Sexual Self‐Rating Scale (SSRS) and the Process Outcome Specific Measure (POSM) to assess the new questionnaire's validity. Internal consistency was measured using Cronbach's alpha. Test–retest reliability was calculated using quadratic weighted kappa. Results The VIN questionnaire had a high degree of internal consistency (Cronbach's alpha, 0.89). Test–retest reliability was assessed, with most questions showing a quadratic weighted kappa value of 0.5 or above. Most questions showed a stronger correlation with the corrected total VIN score than with HADS anxiety and depression subscales and the SSRS, indicating discriminant validity. Most questions correlated significantly with the DLQI and POSM scores, indicating convergent validity. Conclusions Initial assessment of the VIN questionnaire demonstrated that it is a valid and reliable measure of the burden of disease for women. The questionnaire could be used to compare new and existing treatments for VIN or to assess or monitor the impact of care.